TINDAK PIDANA DENGAN SENGAJA DAN DIRENCANAKAN LEBIH DAHULU MERAMPAS NYAWA ORANG LAIN (PUTUSAN NOMOR 108/PID.B/2021/PN STB): Crime of Intentionally and Premeditatedly Depriving Another Person of Life (Case Number 108/Pid.B/2021/Pn Stb) - Tato, Susan Putri Simon; Multiwijaya, Vientje Ratna (AMICUS CURIAE, 2024)
The crime of intentionally and premeditatedly seizing the lives of other people is the act of someone who has previously planned to take the lives of others by taking a piece of wood to beat the victim which resulted in the death of the victim in decision number 108/Pid.B/2021/PN .stb . The main issues raised 1.) Was the act of the perpetrator of the crime intentionally and planned beforehand to take the lives of other people right or not according to Article 338 of the Criminal Code?; 2.) How is the punishment for the perpetrators of the crime intentionally and planned beforehand to take the lives of others, is it appropriate or not with the aim of punishment? This study uses a normative research type that is descriptive analysis, using secondary data obtained from a literature study which is processed qualitatively with the conclusion that (1) The actions of the perpetrators of criminal acts deliberately and premeditated to take other people's lives are not appropriate with Article 338 of the Criminal Code. (2) The sentencing of the perpetrators of criminal acts with intention and premeditation to take other people's lives is not appropriate with the aim of sentencing because they are only sentenced to 13 years in prison. The results of the defendant's research are related to the purpose of punishment, namely 3R 1D, in which the perpetrator should be subject to Article 340 of the Criminal Code with a sentence of 20 years in prison.